2(5c+2)-2c=3(2c=3)=7

Simple and best practice solution for 2(5c+2)-2c=3(2c=3)=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(5c+2)-2c=3(2c=3)=7 equation:



2(5c+2)-2c=3(2c=3)=7
We move all terms to the left:
2(5c+2)-2c-(3(2c)=0
We add all the numbers together, and all the variables
-2c+2(5c+2)-(32c=0
We multiply parentheses
-2c+10c-(32c+4=0
We add all the numbers together, and all the variables
8c-(32c+4=0

You can always share this solution

See similar equations:

| 5^2x+5=12^x | | 5(2y-1)-4(y-3)=20 | | 1^x=5x+2 | | -3(4p-2)=2(p-1) | | 4(x-1)+4x-1=4 | | (w-7)(w-9)=0 | | 5(9-4x)=40 | | 3(5x-7)=4 | | 3u+1=u+8 | | 2u+8=4+u | | 16a-21=20a+3 | | 10^2x=75 | | 16=n3/4 | | 7-5m=3m-1 | | 67w–71w+40w=72 | | x-(1237.5+0.25(x-12000)=30000 | | x-(1237.5+((0.25(x-12000))=30000 | | 2(x+9)?2=52?7x | | x=1237.5+0.25x-3000 | | -5+6(1+3x)=-23 | | 5x-7-2x+4=27 | | 1237.5+0.25x-3000=x | | 8k+46=10k=25 | | 2(m-1)=3(2m-4) | | 23m-16=20m-19 | | 15^x/2^x=4 | | 5t-18=9t-26 | | -31/2=1/2x+1/2x+ | | 5(y-1)+4(2y-3)=3(2y-7)-(y+4) | | 7x/5=2 | | 6x²-12x-30=0 | | y-60=2-30y |

Equations solver categories